Exploration of Clinical Breakpoint of Danofloxacin for Glaesserella parasuis in Plasma and in PELF - Zihui Xu; Anxiong Huang; Xun Luo; Peng Zhang; Lingli Huang; Xu Wang; Kun Mi; Shiwei Fang; Xiao Huang; Jun Li; Zonghui Yuan; Haihong Hao (Antibiotics, 2021)
Background: In order to establish the clinical breakpoint (CBP) of danofloxacin against G. parasuis, three cutoff values, including epidemiological cutoff value (ECV), pharmacokinetic-pharmacodynamic (PK-PD) cutoff value (COPD) and clinical cutoff value (COCL), were obtained in the present study. Methods: The ECV was calculated using ECOFFinder base on the MIC distribution of danfloxacin against 347 G. parasuis collected from disease pigs. The COPD was established based on in vivo and ex vivo PK-PD modeling of danofloxacin both in plasma and pulmonary epithelial lining fluid (PELF) using Hill formula and Monte Carlo analysis. The COCL was established based on the relationship between the possibility of cure (POC) and MIC in the clinical trials using the “WindoW” approach, nonlinear regression and CART analysis. Results: The MIC50 and MIC90 of danofloxacin against 347 G. parasuis were 2 μg/mL and 8 μg/mL, respectively. The ECV value was set to 8 μg/mL using ECOFFinder. Concentration-time curves of danofloxacin were fitted with a two-compartment PK model. The PK parameters of the maximum concentration (Cmax) and area under concentration-time curves (AUC) in PELF were 3.67 ± 0.25 μg/mL and 24.28 ± 2.70 h·μg/mL, higher than those in plasma (0.67 ± 0.01 μg/mL and 4.47 ± 0.51 h·μg/mL). The peak time (Tmax) in plasma was 0.23 ± 0.07 h, shorter than that in PELF (1.61 ± 0.15 h). The COPD in plasma and PELF were 0.125 μg/mL and 0.5 μg/mL, respectively. The COCL calculated by WindoW approach, nonlinear regression and CART analysis were 0.125–4 μg/mL, 0.428 μg/mL and 0.56 μg/mL, respectively. The 0.5 μg/mL was selected as eligible COCL. The ECV is much higher than the COPD and COCL, and the clinical breakpoint based on data in plasma was largely different from that of PELF. Conclusions: Our study firstly established three cutoff values of danofloxacin against G. parasuis. It suggested that non-wild-type danofloxacin-resistant G. parasuis may lead to ineffective treatment by danofloxacin.